CHANGES IN SLEEP QUALITY FROM ACUPRESSURE AND MASSAGE COMBINED WITH THREAD IMPLANTATION: A CLINICAL INTERVENTION STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the changes in sleep quality and safety of acupuncture combined with manual acupressure massage in patients with sleep disorders of the Heart-Spleen deficiency type.Subjects and methods: A controlled clinical intervention study was conducted on 60 patients diagnosed with sleep disorders of the Heart-Spleen deficiency type at Thai Binh Traditional Medicine Hospital (from January 2025 to May 2025). The study group (n = 30) received acupuncture thread embedding combined with acupressure massage, whereas the control group (n = 30) received acupressure massage only for 15 days.Results: After treatment, the sleep duration of the study group increased from 3.20 ± 0.49 hour/night to 4.13 ± 0.52 hour/night (p < 0.05). The percentage of patients achieving sleep efficacy (≥ 85%) in the study group (26.7%) was higher than in the control group (16.7%) (p < 0.05). The average total PSQI score in the study group decreased significantly from 13.87 ± 3.12 to 4.53 ± 1.12 (p < 0.05). No serious adverse effects were recorded.Conclusion: The combined treatment protocol of thread embedding and acupressure massage has shown significant and safe improvements in sleep quality.
Keywords: Sleep disorders, Insomnia, Heart-Spleen deficiency, thread embedding, acupressure massage, PSQI.